Ultrafast Phenomena XVI Proceedings of the 16th International Conference, Palazzo dei Congressi Stresa, Italy, June 9--13, 2008 - Corkum, Paul.; Silvestri, Sandro; Nelson, Keith A.; Riedle, Eberhard; Schoenlein, Robert W.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
Ultrafast Phenomena XVI presents the latest advances in ultrafast science, including both ultrafast optical technology and the study of ultrafast phenomena. It covers picosecond, femtosecond and attosecond processes relevant to applications in physics, chemistry, biology, and engineering. Ultrafast technology has a profound impact in a wide range of applications, amongst them biomedical imaging, chemical dynamics, frequency standards, material processing, and ultrahigh speed communications. This book summarizes the results presented at the 16th International Conference on Ultrafast Phenomena and provides an up-to-date view of this important and rapidly advancing field.
Attosecond and High-Order Harmonic Generation and Measurement, Atomic and Molecular Physics -- Ultrafast X-ray and Electron Science -- Correlated Electron Systems, Magnetization and Spin Dynamics -- Physics - Condensed Phase and Low Dimensional Systems -- Chemistry - Condensed Phase -- Chemistry - Advanced Spectroscopy, Molecular Control, Hydrogen Bonding, Liquids and Interfaces -- Biological Systems, Molecular Light Harvesting and Charge-Transfer Complexes -- THz Science and Technology, Nano-Optics and Plasmonics -- Novel Pulsed Sources: oscillators, amplifiers, nonlinear mixing -- Frequency Combs and Waveform Synthesis -- Optics, Optoelectronics, Measurement, Diagnostics and Instrumentation -- Applications of Ultrashort Pulses.
Keywords: Physics; Optics; Electrodynamics; Optoelectronics; Plasmons (Physics).; Physics; Optics and Electrodynamics; Optics, Optoelectronics, Plasmonics and Optical Devices; Electronic books